A flow strategy for the rapid, safe and scalable synthesis of N-H 1, 2, 3-triazoles via acetic acid mediated cycloaddition between nitroalkene and NaN3. Issue 27 (6th July 2017) - Li, Dong; Liu, Lei; Tian, Yu; Ai, Yongjian; Tang, Zhike; Sun, Hong-bin; Zhang, Gang
Abstract: The N-unsubstituted 4-aryl-1H-1, 2, 3-triazoles were synthesized via the acetic acid promoted cycloaddition between β-nitrostyrenes with sodium azide under transition-metal-free conditions in a continuous flow microreactor. The continuous-flow microreactor provided a safe environment for the dangerous reagents NaN3 and nitroalkene, and offered such a rapid procedure that the triazoles were formed in less than 4 min. In addition, the excess sodium azide was quenched by the by-product HNO2 in the presence of acetic acid. The scale-up experiment proved again that the yield did not drop in the flow reaction. Moreover, the synthesis of N-unsubstituted 1, 2, 3-triazole was also explored via a one pot reaction with aldehyde, nitromethane and sodium azide, and this reaction was monitored with an "in-tube retention time gradient" (IT-RTG) technology, which may be a novel application of the continuous-flow microreactor. Graphical abstract: